A novel circulating biomarker lnc‐MALAT1 for acute myocardial infarction: Its relationship with disease risk, features, cytokines, and major adverse cardiovascular events. Issue 12 (15th November 2022) - Li, Ruirui; Jin, Jin; Liu, Enxiang; Zhang, Jun
Abstract: Objective: Long noncoding RNA MALAT1 (lnc‐MALAT1) modulates atherosclerotic progression, myocardial ischemia injury, and systematic inflammation, which may be closely involved in acute myocardial infarction (AMI) pathogenesis. Thus, the current study intended to explore the relationship of lnc‐MALAT1 to disease risk, features, cytokines, and prognostication in AMI patients. Methods: This multicenter study consecutively enrolled 160 newly diagnosed AMI patients and 50 controls (angina pectoris patients). Their peripheral blood mononuclear cells were obtained to measure lnc‐MALAT1 by RT–qPCR. Serum cytokines in AMI patients were detected by ELISA. In addition, AMI patients were followed up for major adverse cardiovascular event (MACE) risk evaluation. Results: Lnc‐MALAT1 was higher in AMI patients than in controls (median: 2.245 vs. 0.996, p  = 0.004), and it also presented a good capacity for differentiating AMI patients from controls with an area under the curve of 0.823. Lnc‐MALAT1 was positively related to C‐reactive protein ( p  = 0.005), low‐density lipoprotein cholesterol ( p  = 0.022), cardiac troponin I ( p  = 0.021), and infarct size ( p  = 0.007), but not other biochemical indexes in AMI patients. Meanwhile, lnc‐MALAT1 was positively associated with tumor necrosis factor‐alpha ( p  = 0.001), interleukin (IL)‐6 ( p  = 0.031), IL‐17A ( p  = 0.042), vascular cell adhesion molecule‐1 ( p  = 0.004), and intercellular adhesion molecule‐1 ( p  = 0.021) among AMI patients. Importantly, after categorization, lnc‐MALAT1 high (vs. low) was related to an elevated MACE accumulation rate ( p  = 0.035); furthermore, a higher lnc‐MALAT1 quartile showed a trend to be linked with an increased MACE accumulation rate ( p  = 0.092). Conclusion: Lnc‐MALAT1 may serve as a biomarker for AMI risk, infarct size, inflammation and prognosis, but further validation by large‐scale studies is needed. Abstract : This multicenter study consecutively enrolled 160 newly diagnosed acute myocardial infarction (AMI) patients and 50 controls (angina pectoris patients), their peripheral blood mononuclear cells were obtained to measure long noncoding RNA MALAT1 (lnc‐MALAT1) by RT–qPCR. Serum cytokines were detected by ELISA and major adverse cardiovascular event (MACE) rate was calculated in AMI patients. Lnc‐MALAT1 was higher in AMI patients than in controls (median: 2.245 vs. 0.996, p  = 0.004). Lnc‐MALAT1 was positively related to CRP ( p  = 0.005), LDL‐C ( p  = 0.022), CTnI ( p  = 0.021), and infarct size ( p  = 0.007) but no other biochemical indexes in AMI patients. Meanwhile, lnc‐MALAT1 was positively associated with TNF‐α ( p  = 0.001), IL‐6 ( p  = 0.031), IL‐17A ( p  = 0.042), VCAM‐1 ( p  = 0.004), and ICAM‐1 ( p  = 0.021) among AMI patients. Importantly, after categorization, lnc‐MALAT1 high (vs. low) predicted an elevated MACE accumulation rate ( p  = 0.035); furthermore, a higher lnc‐MALAT1 quartile showed a trend to estimate an increased MACE accumulation rate ( p  = 0.092). Conclusively, lnc‐MALAT1 exhibits the potential to serve as a circulating biomarker for AMI risk, infarct size, inflammation and prognosis.